2009
DOI: 10.4049/jimmunol.0803017
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mast Cell Activation in Gene-Targeted Mice Lacking the Serum- and Glucocorticoid-Inducible Kinase SGK1

Abstract: The PI3K pathway plays a pivotal role in the stimulation of mast cells. PI3K-dependent kinases include the serum- and glucocorticoid-inducible kinase 1 (SGK1). The present study explored the role of SGK1 in mast cell function. Mast cells were isolated from bone marrow (BMMC) of SGK1 knockout mice (sgk1−/−) and their wild-type littermates (sgk1+/+). The BMMC number as well as CD117, CD34, and FcεRI expression in BMCCs were similar in both genotypes. Upon Ag stimulation of the FcεRI receptor, Ca2+ entry but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…As shown earlier (33), antigen-induced Ca 2ϩ entry, activation of Ca 2ϩ -sensitive K ϩ channels, and degranulation were significantly decreased in BMMCs from sgk1 Ϫ/Ϫ mice. The blunted Ca 2ϩ entry into mast cells was paralleled by a decreased anaphylactic reaction of sgk1 Ϫ/Ϫ mice (33). Furthermore, mast cells lacking STIM1 had impaired Ca 2ϩ influx after stimulation with the immunoglobulin E receptor Fc⑀RI as well as decreased degranulation, cytokine production, and anaphylactic reaction (34).…”
Section: Discussionmentioning
confidence: 98%
“…As shown earlier (33), antigen-induced Ca 2ϩ entry, activation of Ca 2ϩ -sensitive K ϩ channels, and degranulation were significantly decreased in BMMCs from sgk1 Ϫ/Ϫ mice. The blunted Ca 2ϩ entry into mast cells was paralleled by a decreased anaphylactic reaction of sgk1 Ϫ/Ϫ mice (33). Furthermore, mast cells lacking STIM1 had impaired Ca 2ϩ influx after stimulation with the immunoglobulin E receptor Fc⑀RI as well as decreased degranulation, cytokine production, and anaphylactic reaction (34).…”
Section: Discussionmentioning
confidence: 98%
“…Ϫ/Ϫ BMMCs have an impaired FcεRI-dependent degranulation if compared with sgk1 ϩ/ϩ cells (33). Electron microscopy analysis revealed that granules of sgk1 Ϫ/Ϫ BMMCs were not different from sgk1 ϩ/ϩ BMMCs (Fig.…”
Section: As Shown Previously Sgk1mentioning
confidence: 99%
“…The process of F-actin disassembly was shown to be dependent on the increase of intracellular Ca 2ϩ (16,23). On the other hand, a powerful regulator of Ca 2ϩ entry and exocytosis in MCs is the serum-and glucocorticoidinducible kinase SGK1 (9,10,33). SGK1-deficient (sgk1 Ϫ/Ϫ ) MCs have a decreased FcεRI-dependent Ca 2ϩ entry and degranulation, and sgk1 Ϫ/Ϫ mice are thus protected against anaphylactic reaction, pointing to a strongly impaired MC function in vivo (33).…”
Section: Mcs and Sgk1mentioning
confidence: 99%
See 1 more Smart Citation
“…17 SGK1 has previously been reported to regulate a wide variety of carriers and ion channels, including the epithelial Ca 2ϩ channels TRPV5 and TRPV6. 17 Most recently, SGK1 has been shown to be critically important for the Ca 2ϩ entry into mast cells after activation of the IgE receptor, 18 an effect mediated by regulation of Orai1. 19 Furthermore, SGK1 participates in the regulation of renal tubular Na ϩ reabsorption, salt appetite, and thus blood pressure.…”
Section: Introductionmentioning
confidence: 99%